Public participation in conservation of heritage area in Johor Bahru City Centre : a study of the level of awareness and understanding [electronic resource] - Rahayu Ahmad, 1980- author; Norsiah Abdul Aziz; Fakulti Alam Bina (2014)
Thesis (Sarjana Sains (Perancangan Bandar dan Wilayah)) - Universiti Teknologi Malaysia, 2014